Quality of life in the pre- And postoperative periods in spinal fusion and discectomy - Rufca, Gibran Franzoni [UNESP]; Romero, Flavio Ramalho [UNESP]; Rufca, Drielly Lívia Cristino Braga; Da Silva, Bruna; De Oliveira, Catilaine; De Lima, Hellen Juliana (FapUNIFESP (SciELO), 2019)
Objectives: Considering the epidemiological and functional importance of spinal pathologies and the large number of surgeries performed today, the study aimed to evaluate the impact of spinal arthrodesis and discectomy surgeries on patients' quality of life. Methods: This is a retrospective, descriptive, and longitudinal study developed in the neurology and neurosurgery department of a strategic tertiary hospital in an inland town in the state of São Paulo. Data were collected through a telephone interview, using the Oswestry questionnaire (ODI) to assess lumbar pain in patients submitted to surgery in 2014 and 2015. Results: There was an improvement in the ODI results in all the periods analyzed. When the evaluations were subdivided by surgical type, there was an absolute improvement in the median ODI results in all procedures, however, only the cervical spine arthrodesis procedure was not statistically significant, probably due to the low number of procedures analyzed (n = 12). Conclusion: It can be concluded that the current surgical technique can contribute to the improvement of patients' quality of life. Level of Evidence III; Comparative retrospective study.
Keywords: Intervertebral disc displacement; Quality of life; Spinal fusion